TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP SISTEM PEMANCINGAN DENGAN TIKET STUDI KASUS DI DESA RARANG TENGAH KECAMATAN TERARA KABUPATEN LOMBOK TIMUR - Leni Lamdani; Parida Angriani (Nusadaya Journal of Multidiciplinary Studies, 2022)
The fishing system with a ticket is buying and selling by fishing, that is, prospective anglers who wish to participate in this fishing activity are required to pay an amount of Rp. 100,000,-. prospective anglers are given a marker in the form of a wooden stake and an entry ticket, anglers have the right to catch fish for a set time, namely 24 hours (a day and night) and the fish they catch can be brought home without weighing it. The focus studied in this study is related to the ticket fishing system in Rarang Tengah Village, Terara District, East Lombok Regency and related to a review of sharia economic law on the ticket fishing system in Rarang Tengah Village, Terara District, East Lombok Regency. This research method uses a qualitative research type with an analytic descriptive approach. Types and sources in data collection, namely primary data derived from observations and interviews. Secondary data comes from documentation, results of previous research and other sources related to research. Checking the validity of the data is done using peer discussions and triangulation. The results of the study show that the fishing system with tickets in Rarang Tengah Village is not allowed due to one of the conditions in buying and selling, namely goods or objects cannot be handed over directly by the fishing manager to fishing and the object requirements are not fulfilled. Therefore, buying and selling by fishing is prohibited in Islamic law because it contains elements of gharar or ambiguity in it which results in profits and losses experienced by each angler.